Hematologic manifestations of theumatic diseases - Hetman, Marcin; Kulczyński, Marcin; Dobryniewska, Wanda; Grzebyk, Dominik; Fornal, Natalia; Bracik, Ewelina; Chromiec, Tomasz (Journal of Education, Health and Sport, 2018)
Rheumatic diseases are, by their very nature, multisystemic entities with vast array of possible hematologic manifestations. The mechanisms of different hematologic manifestations tend to be complex and vary from patient to patient. The presence of a given hematologic abnormality can, in some instances, be a prognostic factor with varying utility in different disorders. Recent research in basic sciences has contributed to the understanding of hematologic complications of autoimmune diseases. The aim of this work is to give a brief overview of the latest research on the pathophysiology of hematologic manifestations in rheumatic diseases, with epidemiologic considerations included when available. Special attention has been paid to the pathophysiology of anemia and the challenges of its diagnosis.